State health insurance benefit mandates and health care affordability - James Bailey (Journal of Risk and Financial Management, 2022)
Every US state requires private health insurers to cover certain conditions, treatments, and providers. These benefit mandates were rare as recently as the 1960s, but the average state now has more than forty. These mandates are intended to promote the affordability of necessary health care. This study aims to determine the extent to which benefit mandates succeed at this goal. Using fixed effects and difference-in-difference research designs with data from the restricted Medical Expenditure Panel Survey-household Component (MEPS-HC), it provides the first empirical estimates of how health insurance benefit mandates affect out-of-pocket costs and total spending on health care. Both strategies find that mandates significantly reduce out-of-pocket spending, but they are divided on whether mandates also reduce overall health care spending and spending by private insurers.
Keywords: 330; benefit mandates; out of pocket spending; health care affordability; Medical Expenditure Panel Survey